2008
DOI: 10.1097/mnh.0b013e328305b9a5
|View full text |Cite
|
Sign up to set email alerts
|

Do thiazides worsen metabolic syndrome and renal disease? The pivotal roles for hyperuricemia and hypokalemia

Abstract: Purpose of review-1. To review the current controversies related to the use of thiazide diuretics as first-line treatment of hypertension 2. To discuss the causal roles for hyperuricemia and hypokalemia on the adverse consequences of thiazide usage Recent findings-Thiazides significantly reduce morbidity and mortality in hypertensive subjects. However, there remains debate about thiazide usage as first line treatment of hypertension. This negative impact of thiazides may be partially attributed to the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 74 publications
1
33
0
4
Order By: Relevance
“…No change was noted in our LH group. Usually, when thiazide therapy is initiated, a modest increase in creatinine levels may occur due to volume contraction [Reungjui et al 2008], and such an effect was found in the Nishiwaki trial [Nishiwaki et al 2013], but not by our group.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…No change was noted in our LH group. Usually, when thiazide therapy is initiated, a modest increase in creatinine levels may occur due to volume contraction [Reungjui et al 2008], and such an effect was found in the Nishiwaki trial [Nishiwaki et al 2013], but not by our group.…”
Section: Discussionmentioning
confidence: 89%
“…Tsouli and colleagues reported that nifedipine and verapamil have no effect, whereas amlodipine and felodipine decrease serum uric acid levels [Tsouli et al 2006]. Recent studies suggest that hyperuricemia induced by thiazides can be associated with increased cardiovascular risk [Reungjui et al 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Low S K levels affect myocardial resting membrane potential, which increases the probability of ventricular arrhythmias and sudden cardiac death (11). Hypokalemia can also predispose patients to developing diastolic dysfunction, digoxin toxicity, and insulin resistance, all of which increase the risk for cardiovascular events and death (12)(13)(14)(15)(16). Dietary potassium depletion has been linked to the genesis of hypertension, and supplementation can improve BP control (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…These nutrients have been shown to counter the effects of fructose in animal models, and controlling for these factors can be difficult. 30,31 Contrary to natural fruits, because dried fruits are deprived of their natural content of vitamins and antioxidants and yet maintain a high fructose content when processed, they were included in the analysis. For each questionnaire, the total intake of grams of fructose per day was determined.…”
Section: Primary Predictor and Outcomementioning
confidence: 99%